A mutation in Asparagine‐Linked Glycosylation 12 (ALG12) leads to receptor misglycosylation and attenuated responses to multiple microbial elicitors. Issue 15 (15th June 2020) - Trempel, Fabian; Eschen‐Lippold, Lennart; Bauer, Nicole; Ranf, Stefanie; Westphal, Lore; Scheel, Dierk; Lee, Justin
Abstract : Changes in cellular calcium levels are one of the earliest signalling events in plants exposed to pathogens or other exogenous factors. In a genetic screen, we identified an Arabidopsis thaliana 'changed calcium elevation 1' ( cce1 ) mutant with attenuated calcium response to the bacterial flagellin flg22 peptide and several other elicitors. Whole‐genome resequencing revealed a mutation in asparagine‐linked glycosylation 12 that encodes the mannosyltransferase responsible for adding the eighth mannose residue in an α‐1, 6 linkage to the dolichol‐PP‐oligosaccharide N ‐glycosylation glycan tree precursors. While properly targeted to the plasma membrane, misglycosylation of several receptors in the cce1 background suggests that N ‐glycosylation is required for proper functioning of client proteins. Abstract :